2010
DOI: 10.1509/jmkg.74.3.107
|View full text |Cite
|
Sign up to set email alerts
|

Bye-Bye Bundles: The Unbundling of Music in Digital Channels

Abstract: Fueled by digital distribution, unbundling is prevalent in many information and entertainment industries. What is the effect of this unbundling on sales, and what bundle characteristics drive this effect? I empirically examine these questions in the context of the music industry, using data on weekly digital-track, digital-album, and physical-album sales from January 2005 to April 2007 for all titles released by a sample of over 200 artists. My modeling framework, a system of an "album-sales" and a "song-sales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 55 publications
1
68
1
4
Order By: Relevance
“…Our focus on dynamics and complementary goods in a two-sided market as opposed to examining related goods of the same type makes both our methodology and result very different from other empirical work on bundling related to content industries like music and cable TV, where studies have demonstrated that mixed bundling can actually reduce revenues and profitability compared to pure bundling [Crawford, 2008, Elberse, 2010; in contrast, we find that dynamics make bundling more profitable.…”
Section: Related Literaturecontrasting
confidence: 66%
“…Our focus on dynamics and complementary goods in a two-sided market as opposed to examining related goods of the same type makes both our methodology and result very different from other empirical work on bundling related to content industries like music and cable TV, where studies have demonstrated that mixed bundling can actually reduce revenues and profitability compared to pure bundling [Crawford, 2008, Elberse, 2010; in contrast, we find that dynamics make bundling more profitable.…”
Section: Related Literaturecontrasting
confidence: 66%
“…Second, the digitization of music allows the unbundling of albums and in the digital world customers download singles increasingly. This means that the downloads are not as rewarding as previous CD sales were (Elberse 2010). To address these two problems, there are a number of new distribution concepts, one of which is Music as a Service (MaaS).…”
Section: Introductionmentioning
confidence: 99%
“…As a discipline, Marketing has relied more on IT, Economics and CS for its data analytics. From channel choice to prices and recommendation systems, music bundling and online reviews, and social networks, interdisciplinary researchers have conducted impactful analytics research [19,28]. Many different sources of data have been used, and there has been substantive mastery of the collection and analysis of Web data.…”
Section: Creating the Policy Analytics Fusionmentioning
confidence: 99%